Forage palm silage in complete diet (Research, Society and Development, 2022)
The objective was to evaluate the qualitative aspects of forage cactus silage associated with corn straw (CS) or elephant grass (EG) as a forage source in a complete diet. Two sources of forage (SC and EG) and four levels of replacement of sorghum meal by forage cactus (0%, 33%, 66% and 100%) were evaluated, with 5 replications. The diet containing CS had higher content of TDN, CP, MM, EE and CNF and lower content of DM, NDFap, LIG, NDFi and total CHO. For the levels of replacement of sorghum bran by forage cactus there was a decreasing linear effect for DM, LIG, Total CHO, NFC, NDFap, NDFi and increasing for MM. Greater loss and lesser recovery of DM were observed in the diet with CS at the levels of 33 and 66% replacement. For each 1% replacement, there was a 0.088g decrease in DM loss for the CS diet. The diet containing EG replacement levels showed quadratic behavior, with the replacement level with the lowest DM loss being 11.45%. For each 1% replacement of sorghum bran by forage cactus in the CS diet, there was a 0.061g decrease in DM recovery. The diet containing EG replacement levels showed quadratic behavior, with a maximum replacement point of 38.5%, with 90% DM recovery. The forage palm can replace 35 to 55% of sorghum meal in complete diet silage when associated with CS or EG.